The impact of the residential built environment on work at home adoption frequency: An example from Northern California - Wei (Laura) Tang; Patricia Lyon Mokhtarian; Susan L. Handy (Journal of Transport and Land Use)
Working at home is widely viewed as a useful travel-reduction strategy, and it is partly for that reason that considerable research related to telecommuting and home-based work has been conducted in the last two decades. This study examines the effect of residential neighborhood built environment (BE) factors on working at home. After systematically presenting and categorizing various relevant elements of the BE and reviewing related studies, we develop a multinomial logit (MNL) model of work-at-home (WAH) frequency using data from a survey of eight neighborhoods in Northern California. Potential explanatory variables include sociodemographic traits, neighborhood preferences and perceptions, objective neighborhood characteristics, and travel attitudes and behavior. The results clearly demonstrate the contribution of built environment variables to WAH choices, in addition to previously-identified influences such as sociodemographic predictors and commute time. BE factors associated with (neo)traditional neighborhoods were associated both positively and negatively with working at home. The findings suggest that land use and transportation strategies that are desirable from some perspectives will tend to weaken the motivation to work at home, and conversely, some factors that seem to increase the motivation to work at home are widely viewed as less sustainable. Accordingly, this research points to the complexity of trying to find the right balance among demand management strategies that sometimes act in competition rather than in synergy.